Time of day affects MrgD-dependent modulation of cardiomyocyte contractility - Monteiro, André L. L.; Eliezeck, Marcos; Scalzo, Sérgio R. A.; Silva, Mário Morais; Sanches, Bruno; Ferreira, Katyana K. S.; Poletini, Maristela O.; Peliciari-Garcia, Rodrigo A.; Cau, Stêfany B. A.; Souza Santos, Robson A.; Guatimosim, Silvia (American Journal of Physiology: Cell Physiology, 2024)
Alamandine, a member of the renin-angiotensin system, serves critical roles in cardioprotection, including the modulation of cardiomyocyte contractility. Whether this effect varies along the day is unknown. Our results provide evidence that alamandine via receptor MrgD exerts opposing actions on cardiomyocyte shortening, enhancing, or reducing contraction depending on the time of day. These findings may have significant implications for the development and effectiveness of future cardiac therapies. The renin-angiotensin system (RAS) is composed of a series of peptides, receptors, and enzymes that play a pivotal role in maintaining cardiovascular homeostasis. Among the most important players in this system are the angiotensin-II and angiotensin-(1–7) peptides. Our group has recently demonstrated that alamandine (ALA), a peptide with structural and functional similarities to angiotensin-(1–7), interacts with cardiomyocytes, enhancing contractility via the Mas-related G protein-coupled receptor member D (MrgD). It is currently unknown whether this modulation varies along the distinct phases of the day. To address this issue, we assessed the ALA-induced contractility response of cardiomyocytes from mice at four Zeitgeber times (ZTs). At ZT2 (light phase), ALA enhanced cardiomyocyte shortening in an MrgD receptor-dependent manner, which was associated with nitric oxide (NO) production. At ZT14 (dark phase), ALA induced a negative modulation on the cardiomyocyte contraction. β-Alanine, an MrgD agonist, reproduced the time-of-day effects of ALA on myocyte shortening. N G -nitro-l-arginine methyl ester, an NO synthase inhibitor, blocked the increase in fractional shortening induced by ALA at ZT2. No effect of ALA on myocyte shortening was observed at ZT8 and ZT20. Our results show that ALA/MrgD signaling in cardiomyocytes is subject to temporal modulation. This finding has significant implications for pharmacological approaches that combine chronotherapy for cardiac conditions triggered by disruption of circadian rhythms and hormonal signaling. NEW & NOTEWORTHY Alamandine, a member of the renin-angiotensin system, serves critical roles in cardioprotection, including the modulation of cardiomyocyte contractility. Whether this effect varies along the day is unknown. Our results provide evidence that alamandine via receptor MrgD exerts opposing actions on cardiomyocyte shortening, enhancing, or reducing contraction depending on the time of day. These findings may have significant implications for the development and effectiveness of future cardiac therapies.